2020
DOI: 10.21203/rs.3.rs-22942/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions on preeclampsia and eclampsia among older women in rural southwestern Uganda

Abstract: Background Eclampsia is among the leading causes of maternal mortality. It is a serious hypertensive (HT) complication of pregnancy and increases the risk of cardiovascular disease (CVD) in later life. Pregnancy-related HT complications predispose to chronic hypertension and premature heart attacks. A significant proportion of women with preeclampsia/eclampsia does not reach the formal healthcare system or arrive too late because of certain African cultural beliefs about the condition. The older senior women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…This may lead to tension headache. A qualitative study conducted in rural Southwestern Uganda on perceptions on preeclampsia and eclampsia among senior, older women, revealed that marital tension was associated with PE-E [37]. This is consistent with the findings in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This may lead to tension headache. A qualitative study conducted in rural Southwestern Uganda on perceptions on preeclampsia and eclampsia among senior, older women, revealed that marital tension was associated with PE-E [37]. This is consistent with the findings in this study.…”
Section: Discussionsupporting
confidence: 90%